OPTIMIZATION ANALYSIS ON THE USE OF PRODUCTION INPUT FARMING CUCUMBER - Sasmita Siregar; Khairunnisa Rangkuti; Norman (AGRIUM: Jurnal Ilmu Pertanian, 2016)
This research aims to determine the effect of the use of land area, labor, seed, fertilizer, and pesticides / stimulants against cucumber production in cultivation in the research location.Furthermore it also to determine the optimization level of the use of production inputs as well as the feasibility of the cultivation.In obtaining the data used qualitative research method which is a case study. Selection of research location is done purposely.Sample selection method is using Simple Random Sampling with the sample size as many as 30 people.Data analysis method using the model of Cobb–Douglas production function, output elasticity, R/C and B/C financial analysis, and descriptively. The research result,use of production inputs simultaneously affect production significantly, while partially, production inputs which significantly affect the increase in production is land area and fertilizer, while other production inputs ie seed, labor, and pesticide / stimulants not affect production significantly.Level optimization of production inputs land area and fertilizer yet efficient, while production inputs seed, tenaga kerja, and pesticides / stimulants not efficient. Cultivation of cucumber  in the research location deserve to be developed.Key Words: Optimization, Production Input, Cucumber